Hubungan Tingkat Pengetahuan Pedagang, Lokasi Berjualan, dan Tingkat Higenis dengan Kandungan Logam Berat Timbal (Pb) pada Gorengan di Surabaya Timur - Felicia Anggono; Trias Mahmudiono (Media Gizi Kesmas, 2023)
Background: Lead (Pb) is a type of heavy metal that can interfere with human health. Fritters is one of the favorite snacks for Indonesian people because it has delicious taste and cheap. One of the sources of lead (Pb) pollution in fritters is fritters which are heavy polluted by motor vehicle fumes. Objectives: to know the relationship between the level of knowledge, the location of selling and the level of hygiene of traders with the content of lead (Pb) in fritters in East Surabaya. Methods: This research was an analytic observational study.  40 Samples were taken at random for each selected trader in East Surabaya, one sample of fritters was taken which was purchased the most by people. The sample had been tested qualitatively using the easy kit. Analysis of the relationship between the level of knowledge, the location of selling, and the level of hygiene using the chi-square test. Results: Based on research conducted that there are 11 samples of fritters sold in East Surabaya contaminated with lead (Pb). In addition, there is a significant relationship (p=0.046) between the location of sale and the results of the lead (Pb) content in fritters. The level of hygiene and the lead (Pb) content results in fritters had a significant relationship (p=0.046). Conclusions: There was still lead (Pb) contamination in fritters in East Surabaya. Traders also need to increase their knowledge of food contamination and pay attention to where to sell and maintain hygiene and sanitation.